PERAWATAN AHU (AIR HANDLING UNIT) PADA SISTEM PENDINGINAN DI HOTEL S JAKARTA - Al Zabal, Muhamad Yori; Utama, Hadian Satria (Jurnal Serina Abdimas, 2024)
AHU (Air handling unit) is a mechanical system installed in buildings to regulate indoor air conditions. AHU works by taking air from outside and flowing it through a filter to remove existing particles such as dust, pollen and other pollutants. AHU maintenance in hotel buildings is a routine thing that is carried out to maximize the performance of the AHU. AHU is one of the key components in the HVAC (Heating, Ventilation, and Air conditioning) system which is responsible for air circulation in the building. Engineering at the hotel carries out maintenance, namely cleaning filters, cooling coils and strainers. Cleaning the AHU greatly influences the temperature produced by the AHU itself. If the filter and cooling coil are covered by existing pollutants, it will be very difficult for the cooling coil to produce cold even though the chiller water supply has met the desired cold standards. Engineering at Hotel S carries out maintenance on the AHU, namely cleaning at least once a month to minimize damage to the AHU and also the temperature produced by the AHU itself remains at the desired stable temperature. The implementation method is action research to solve problems or improve certain situations. The results obtained are that proper and regular maintenance of the AHU is very important to ensure indoor air quality remains good, maintain guest comfort, and increase energy efficiency, because guest comfort is a top priority at Hotel S.